(untitled) (Lectio: Journal of Language and Language Teaching, 2021)
This study was conducted to answer the following questions: 1. What are the cognitive strategies employed by high and low achievers?. 2. What are the differences in cognitive strategies employed by high and low achievers? The participants were 6 second-year students from the English Education Study Program with 3 students who are considered as high achievers and 3 others as low achievers in reading. To obtain the data, three times observation and retrospective interviews have been conducted. The topics of the reading text for the 3 meetings were all different. The results of the research are: 1. The high achiever students have reportedly used 8, 5, and 6 cognitive strategies and low achiever students have reportedly used 3, 4, and 7 out of 10 cognitive strategies. 2. There were two major differences in employing the cognitive strategies in terms of the total amount of cognitive strategies used and the way high and low achievers employed the strategies.